Pengaruh Current Ratio, Debt To Equity Ratio dan Return On Equity Terhadap Return Saham Pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia - Abdurrohman Oman; Dwi Fitrianingsih; Anis Fuad Salam; Hurul Aeni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the influence of Current Ratio (CR) Debt to Equity Ratio (DER) and Return On Equity on Stock Returns either partially or simultaneously in Property and Real Estate Companies listed on the Indonesian Stock Exchange in the 2014-2018 period. This research uses descriptive statistical analysis research type with a quantitative approach. The population in this study amounted to 64 companies. This study uses financial statement data with time series for the last 5 years. Sampling in this study using purposive random sampling technique and obtained a sample of 15 companies. The results of the analysis using the t test and f test state that Current Ratio, Debt to Equity Ratio and Return On Equity have a significant effect on Stock Returns either partially or simultaneously. Keyword : Current Ratio, Debt to Equity Ratio and Return On Equity Against Stock Return